2011
DOI: 10.1002/adma.201101960
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Dispersibility Tuning of Carbon Nanotubes by a Water‐Soluble Stilbene as a Dispersant

Abstract: A water‐soluble stilbene derivative with cationic charges enables tuning of the dispersibility of the single‐walled carbon nanotubes (SWNTs) in aqueous solution by photoirradiation. The nearly coplanar core of the stilbene dispersant interacts with the SWNTs via π–π interactions, resulting in a stable dispersion of the SWNTs. Photoinduced cyclization for the dispersant‐triggered reprecipitation of the SWNTs is due to detachment of the dispersant from SWNTs surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…[41] UV irradiation reversibly induces a change in the surface property of the carbon nanotubes, which indicates a possibility to control the dispersion/aggregation behavior. Matsuzawa et al reported the photoinduced dispersibility tuning of carbon nanotubes using water-soluble stilbene adsorbed on the surface by p-p interactions.…”
Section: Improved Functionality By the Formation Of Metal Oxide Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…[41] UV irradiation reversibly induces a change in the surface property of the carbon nanotubes, which indicates a possibility to control the dispersion/aggregation behavior. Matsuzawa et al reported the photoinduced dispersibility tuning of carbon nanotubes using water-soluble stilbene adsorbed on the surface by p-p interactions.…”
Section: Improved Functionality By the Formation Of Metal Oxide Layersmentioning
confidence: 99%
“…Matsuzawa et al reported the photoinduced dispersibility tuning of carbon nanotubes using water-soluble stilbene adsorbed on the surface by p-p interactions. [41] UV irradiation reversibly induces a change in the surface property of the carbon nanotubes, which indicates a possibility to control the dispersion/aggregation behavior. By applying this type of technique to the CFs, one can realize a stimuli-responsive coating of various nanoparticles including metals, metal oxides, and polymers.…”
Section: Improved Functionality By the Formation Of Metal Oxide Layersmentioning
confidence: 99%
“…We are actively working on the preparation of a new electrolyte gelator, and various derivatives are prepared by a co-polymerization method using two types of monomers, and high gelation capacity has been observed. [13] For the CNT dispersion function, we succeeded in enhancing the function such as addition of further optical responsivity by developing a material dedicated to the dispersal function, [14] and joint research has been started with a company for industrial realization using CNTs. On the other hand, by using the gelator that was commercialized by an independent research group, an extremely fascinating phenomenon unseen before, that is the asymmetric environment (circular dichroism activity) dependent on the stirring direction of the solution, has been reported (different CD activity is observed in the solution by right-or left-rotational stirring).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In addition, among the SWNTs dispersants, some reactive aromatic compounds [13,14] and polymers [15][16][17] have been reported to control SWNTs dispersion and aggregation by their photochemical or thermal reactions. Condensed aromatic groups such as anthracene or pyrene having π-π interaction with SWNTs are also involved in SWNTs dispersants.…”
Section: Introductionmentioning
confidence: 99%